Implementation of Problem-Based Learning in Changing Perception Petroleum Geoscience Student - Abdul Latiff, A.H. (Springer Science and Business Media Deutschland GmbH, 2022)
This chapter presents the results of the implementation of Problem-Based Learning towards Petroleum Geoscience student in Universiti Teknologi PETRONAS (UTP). The PBL was implemented with emphasise given to the 4th year student majoring in exploration geophysics courses in Petroleum Geoscience program. The work conducted with the intention of encouraging the higher-order thinking skills among the undergraduate students who are taking Bachelor of Science in Petroleum Geoscience program in Univeristi Teknologi PETRONAS. The improvement in studentsâ technical and communicative abilities were examined to determine the extent of their positive and negative attitudes towards project-based learning. It is anticipated that the information gained from this study will benefit both the teachers in their choices of suitable methodologies and studentsâ outcomes with the respect to improved competency in their thinking and problem-solving skills and increased confidence in project-based learning in small groups. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.